The spatial mismatch hypothesis and the use of social networks for job search in Cape Town - Hoekman, Guus (Department of Sociology, 2015)
This dissertation explores the spatial mismatch hypothesis in Cape Town; in particular its mechanisms, how they interact with lower-skilled workers in the labour market, and what role social networks play. The spatial mismatch hypothesis suggests that a significant distance between residential areas and centres of employment (1) leads to a lengthy and expensive commute which makes the job search in economic centres more difficult, (2) reduces the amount of information about job opportunities that is available to lower-skilled workers, and (3) reduces the effectiveness of using one's social network as a means to find out about work opportunities. Through semi-structured, in-depth interviews with lower-skilled workers and employers, this research attempts to offer insights into the mechanisms of the spatial mismatch hypothesis and challenge the assumption that a causal relationship exists between spatial mismatch and the suggested consequences put forward by a literature that is dominated by quantitative studies. Rather than measuring the spatial mismatch, this research is intended to provide possible ways in which the spatial mismatch functions. It does not set out to prove anything in either a qualitative or quantitative way, but rather highlight the gaps in the current interpretation of the spatial mismatch hypothesis in order to gain a better understanding of its mechanisms.